Bones of Contention: Reflections on Osteoarchaeology and the Baltic Region - Bartosiewicz, László (Archaeologia Lituana, 2020)
During the last decade, some of the most significant archaeological interpretations included the integrated use of scientific methods, including osteoarchaeology. The identification, analysis and interpretation of human and animal remains from archaeological sites has been developing along increasingly different trajectories, due to the different aspects of daily life the bones of animals and humans illustrate. This paper is a review of the position osteoarchaeological research has achieved since the 1960s, through the example of its beginnings in the mid-20th century in Sweden. Similarities and differences between the histories, contents of and directions in human and animal osteoarchaeology are reviewed, revealing some controversies in the ways the results of the discipline have been embraced by the broader archaeological community. Similarly to archaeological research, increasingly complex analytical methods help refining results obtained by traditional morphometric methods applied to bones. This trend will continue in the foreseeable future: scientific methods will keep on contributing to valuable insights into past societies. Special sections in the paper are devoted to the possibilities of disseminating the results of osteoarchaeology through formal and informal networks such as publications, teaching and conferences within the context of the Baltic region through the example of archaeozoological research.